2014
DOI: 10.1002/mrm.25384
|View full text |Cite
|
Sign up to set email alerts
|

Dedicated receiver array coil for 1H lung imaging with same‐breath acquisition of hyperpolarized 3He and 129Xe gas

Abstract: An array coil to improve H SNR of the lung in same-breath acquisition with hyperpolarized gases has been demonstrated. Magn Reson Med 74:291-299, 2015. © 2014 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…Trap circuits are commonly used to tune the coil resonance to multiple frequencies using inductive and capacitive elements in parallel. However, for 19 F (60.06 MHz at 1.5 T) and 1 H (63.8 MHz at 1.5 T) the bandwidth of passive traps with the typical Q‐factors of commercially available components is comparable to the frequency separation, limiting their use, as discussed previously . Another approach is to actively switch‐in capacitors in parallel to the existing tuning capacitors using PIN diodes, and more recently the use of field effect transistors and micro‐electromechanical systems (MEMS) have also been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trap circuits are commonly used to tune the coil resonance to multiple frequencies using inductive and capacitive elements in parallel. However, for 19 F (60.06 MHz at 1.5 T) and 1 H (63.8 MHz at 1.5 T) the bandwidth of passive traps with the typical Q‐factors of commercially available components is comparable to the frequency separation, limiting their use, as discussed previously . Another approach is to actively switch‐in capacitors in parallel to the existing tuning capacitors using PIN diodes, and more recently the use of field effect transistors and micro‐electromechanical systems (MEMS) have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, for 19 F (60.06 MHz at 1.5 T) and 1 H (63.8 MHz at 1.5 T) the bandwidth of passive traps with the typical Q-factors of commercially available components is comparable to the frequency separation, limiting their use, as discussed previously. 5 Another approach is to actively switch-in capacitors in parallel to the existing tuning capacitors using PIN diodes, and more recently the use of field effect transistors 6 and micro-electromechanical systems (MEMS) [7][8][9] have also been reported. The equivalent series resistance (ESR) of these three devices are reported to be insignificant when compared with the quality factor (Q) of trap circuit inductors (eg.…”
Section: Introductionmentioning
confidence: 99%
“…The reliance on the 1 H MR system's birdcage body coil for signal reception constrains the signal-tonoise ratio (SNR) in 1 H images of the lung, which is already limited by the low proton density of lung parenchyma. In a recent study (23), we showed that the 1 H lung SNR in same-breath imaging can be improved with a nested 1 H receive array, which is compatible with operation with either a 3 He or a 129 Xe T-R coil.…”
Section: Introductionmentioning
confidence: 94%
“…Both the elements of the dual Helmholtz were fitted with two traps; one trap at the 1 H frequency to enable 1 H imaging with this coil in situ and the other trap to dual-tune the coil to the 129 Xe and 3 He Larmor frequencies. The trap design was based on the formalism established in our earlier study for multituned resonators (23), the frequency of the trap for dual-tuning was 47.81 MHz. A high-pass matching circuit was used to match the coil at both resonant frequencies of 3 He (48.62 MHz) and 129 Xe (17.65 MHz) at 1.5T.…”
Section: He and 129 Xe Dual-tuned Coil Designmentioning
confidence: 99%
See 1 more Smart Citation